2014
DOI: 10.1111/iju.12504
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of traditional and alternative sunitinib treatment schedules in Japanese patients with metastatic renal cell carcinoma

Abstract: Abbreviations & Acronyms AE = adverse events ALP = alkaline phosphatase AS = alternative schedule AST = aspartate aminotransferase ECOG PS = Eastern Cooperative Oncology Group performance status IFN-α = interferon alpha LDH = serum lactate dehydrogenase LLN = lower limit of normal mRCC = metastatic renal cell carcinoma MSKCC = Memorial Sloan-Kettering Cancer Center OS = overall survival PFS = progression-free survival TS = traditional schedule TTF = time to treatment failure ULN = upper limit of normal WBC = w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Patients who are unable to tolerate severe AEs on the schedule 4/2 (either at the standard or a modified dosage) are generally switched to an alternative dosing schedule. In recent years, there has been increasing evidence that the schedule 2/1 is associated with a lower frequency of dose reductions or treatment interruptions and has a comparable or even better oncological outcome than the traditional schedule 4/2, especially in Asian patients [11][12][13]22].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who are unable to tolerate severe AEs on the schedule 4/2 (either at the standard or a modified dosage) are generally switched to an alternative dosing schedule. In recent years, there has been increasing evidence that the schedule 2/1 is associated with a lower frequency of dose reductions or treatment interruptions and has a comparable or even better oncological outcome than the traditional schedule 4/2, especially in Asian patients [11][12][13]22].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies described the clinical benefit of an alternative administration schedule, such as 2 weeks of treatment and 1 week off (2/1) instead of the standard 4 weeks of treatment and 2 weeks off (4/2) schedule . According to the pharmacological data, both schedules were shown to have almost the same amount of time with C 0 in the therapeutic range.…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…1 Owing to its prominent treatment efficacy, sunitinib is one of the most widely prescribed drugs for the treatment of metastatic renal cell cancer (RCC). However, almost all patients experience treatment-related adverse events, such as fatigue, bone marrow suppression, hand-foot syndrome, stomatitis, hypertension or hypothyroidism, 1 and dose modification is required for most patients to continue therapy. The traditional dosing schedule for sunitinib is 50 mg administered daily with the 4 weeks on and 2 weeks off schedule.…”
Section: Editorial Comment Editorial Comment From Dr Yuasa To Efficacmentioning
confidence: 99%
“…The traditional dosing schedule for sunitinib is 50 mg administered daily with the 4 weeks on and 2 weeks off schedule. 1 In order to decrease the toxicity and extend the duration of treatment, a recent study has reported an alternative treatment schedule for sunitinib administration involving the 2 weeks on and 1 week off schedule. 2 In this retrospective study, the altered dosing schedule not only increased patient tolerability, but also increased patient survival duration compared with the traditional schedule regimen.…”
Section: Editorial Comment Editorial Comment From Dr Yuasa To Efficacmentioning
confidence: 99%